2011
DOI: 10.1021/cs200523s
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Biofuel Cell for Oxidation of Glucose to CO2

Abstract: Glucose has been widely studied as a fuel in biofuel cells because it not only is abundant in nature and in the bloodstream but also demonstrates low volatility, is nontoxic, and is inexpensive. Those qualities coupled with its relatively high energy density qualify glucose as a promising fuel. However, one key to efficient use of this substrate as fuel is the ability to oxidize glucose to CO2 and convert, more efficiently, the chemical energy released upon the redox reactions to electrical power. Most glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
91
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(93 citation statements)
references
References 14 publications
1
91
0
1
Order By: Relevance
“…Compared with the six-enzyme EFC that oxidizes glucose to CO 2 (ref. 13), the inherently low, but Supplementary Table S3. promiscuous, activities of one enzyme that catalyses several substrates results in very low power densities. The use of more than ten enzymes for implementing complex reactions for the production of biocommodities, fine chemicals and pharmaceuticals seems to be not economically prohibitive 25,26,[30][31][32][33] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the six-enzyme EFC that oxidizes glucose to CO 2 (ref. 13), the inherently low, but Supplementary Table S3. promiscuous, activities of one enzyme that catalyses several substrates results in very low power densities. The use of more than ten enzymes for implementing complex reactions for the production of biocommodities, fine chemicals and pharmaceuticals seems to be not economically prohibitive 25,26,[30][31][32][33] .…”
Section: Discussionmentioning
confidence: 99%
“…The incomplete oxidation of organic fuels mediated by one or a few enzymes in EFCs results in low energy densities, waste of fuel and inhibition of enzymes by the metabolic products. In vitro synthetic enzymatic pathways have been constructed on the anode compartments in EFCs for deep or complete oxidation of methanol 9,10 , ethanol 11 , glycerol 12 and glucose 13 . However, previous studies did not provide quantitative evidence (for example, Faraday efficiency) for the complete oxidation of organic fuels in microbial fuel cells 14,15 .…”
mentioning
confidence: 99%
“…Mediators have been used to enhance electron transfer rate [6,9,11] and carbon or mesoporous materials with diameters comparable to the size of the enzyme were explored for enhanced enzyme-electrode interactions [12]. The following approaches provide proper enzyme orientation: specific covalent attachment of enzymes to the electrode surface [13,14]; protein engineering …”
Section: Bottom Up Approach: Integration Of Biocatalysts With Differementioning
confidence: 99%
“…In 2011, Xu et al demonstrated the complete oxidation of glucose with a non-natural oxidation pathway. 6 A six-enzyme cascade was utilized to perform a 12-step, 24-electron oxidation of glucose. The power density showed an almost 50-fold increase with the cascade.…”
mentioning
confidence: 99%
“…In this work, we will demonstrate the detailed, mass spectrometric product analysis on a previously reported glucose oxidation system that utilizes a six-enzyme cascade to oxidize glucose to the final product, carbon dioxide. 6 PQQ-dependent glucose, gluconate, alcohol and aldehyde dehydrogenases, oxalate oxidase and aldolase were immobilized on carbon fiber electrodes to perform the complete oxidation of glucose (as shown in Figure 1). The biofuel cell operation products were quantitatively analyzed and the biofuel cell efficiencies were calculated, compared, and discussed.…”
mentioning
confidence: 99%